Comparison of Unenhanced T1-Weighted Signal Intensities Within the Dentate Nucleus and the Globus Pallidus After Serial Applications of Gadopentetate Dimeglumine Versus Gadobutrol in a Pediatric Population. Issue 2 (February 2018) - Renz, Diane M.; Kümpel, Stefanie; Böttcher, Joachim; Pfeil, Alexander; Streitparth, Florian; Waginger, Matthias; Reichenbach, Jürgen R.; Teichgräber, Ulf K.; Mentzel, Hans-Joachim
Abstract : Objective: The aim of this study was to evaluate and compare changes in T1-weighted signal intensity (SI) within the dentate nucleus (DN) and globus pallidus (GP) in a pediatric population after serial applications of the linear gadolinium-based magnetic resonance contrast medium gadopentetate dimeglumine and the more stable macrocyclic agent gadobutrol. Materials and Methods: Institutional review board approval was obtained. Two similar pediatric patient cohorts who underwent at least 3 serial contrast-enhanced magnetic resonance imaging (MRI) examinations with sole application of gadopentetate dimeglumine or gadobutrol were analyzed. All MRI examinations were performed on a 1.5 T system acquiring unenhanced T1-weighted spin echo sequences, which were evaluated on the baseline MRI and after the contrast medium administrations. For analysis of SI changes in the DN, the ratios of the DN to the pons (P) and to the middle cerebellar peduncle (MCP) were assessed. The GP was compared with the thalamus (TH) by dividing the SIs between GP and TH (GP-to-TH ratio). Results: Twenty-eight patients (13 boys, 15 girls; mean age, 8.4 ± 6.8 years) who received at least 3 applications of gadopentetate dimeglumine and 25 patients (13 boys, 12 girls; mean age, 9.7 ± 5.4 years) with 3 or more gadobutrol injections were included. After 3 administrations of gadopentetate dimeglumine, the T1-weighted SI ratios significantly increased: mean difference value of 0.036 ± 0.031 (DN-to-P; P < 0.001), 0.034 ± 0.032 (DN-to-MCP; P < 0.001), and 0.025 ± 0.025 (GP-to-TH; P = 0.001). In a subanalysis of 12 patients with more than 3 injections of gadopentetate dimeglumine, the mean differences of the SI ratios were slightly higher: 0.043 ± 0.032 (DN-to-P; P = 0.001), 0.041 ± 0.035 (DN-to-MCP; P = 0.002), and 0.028 ± 0.025 (GP-to-TH; P = 0.003). In contrast, gadobutrol did not show a significant influence on the SI ratios, neither after 3 nor after more than 3 applications. Conclusions: The T1-weighted SI increase within the DN and GP after serial administrations of the linear contrast medium gadopentetate dimeglumine, but not after serial applications of the macrocyclic agent gadobutrol, found in a pediatric population, is consistent with results published for adult patients. The clinical impact of the intracranial T1-hyperintensities is currently unclear. However, in accordance with the recent decision of the Pharmacovigilance and Risk Assessment Committee of the European Medicines Agency, intravenous macrocyclic agents should be preferred and MR contrast media should be used with caution and awareness of the pediatric brain development in children and adolescents.